2001
DOI: 10.1074/jbc.m008062200
|View full text |Cite
|
Sign up to set email alerts
|

Targeting of Membrane Proteins to the Regulated Secretory Pathway in Anterior Pituitary Endocrine Cells

Abstract: Unlike the neuroendocrine cell lines widely used to study trafficking of soluble and membrane proteins to secretory granules, the endocrine cells of the anterior pituitary are highly specialized for the production of mature secretory granules. Therefore, we investigated the trafficking of three membrane proteins in primary anterior pituitary endocrine cells. Peptidylglycine ␣-amidating monooxygenase (PAM), an integral membrane protein essential to the production of many bioactive peptides, is cleaved and enter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 51 publications
1
23
0
Order By: Relevance
“…To restrict the search for putative trafficking signals to the ADAM10 cytoplasmic tail and minimize effects of other domains, we chose to isolate the contribution of the C-terminal domain by using chimeras with the Tac protein, approach, which has been used extensively to identify ER retention signals (36,37). Immunofluorescence analyses showed that TacADAM10 was not able to reach the cell surface, and demonstrated that the C-terminal domain of ADAM10 is sufficient to prohibit the surface expression of TacADAM10 in heterologous cells.…”
Section: Discussionmentioning
confidence: 99%
“…To restrict the search for putative trafficking signals to the ADAM10 cytoplasmic tail and minimize effects of other domains, we chose to isolate the contribution of the C-terminal domain by using chimeras with the Tac protein, approach, which has been used extensively to identify ER retention signals (36,37). Immunofluorescence analyses showed that TacADAM10 was not able to reach the cell surface, and demonstrated that the C-terminal domain of ADAM10 is sufficient to prohibit the surface expression of TacADAM10 in heterologous cells.…”
Section: Discussionmentioning
confidence: 99%
“…To identify the relevant trafficking signals in NR1 and to minimize effects of NR2 subunits and other NR1 domains, we chose to isolate the contribution of NR1 C-terminal domains using Tac-NR1 chimeras. Such an approach has been used extensively to identify signals involved in secretory and endocytic membrane trafficking (Milgram et al, 1996;Ghosh et al, 1998;Jansen et al, 1998;Tan et al, 1998;El Meskini et al, 2001). The experimental advantages of this ap- proach include the well characterized nature of the Tac protein and its trafficking, the existence of highly specific extracellular epitope antibodies, and the monomeric nature of the Tac chimeras.…”
Section: Discussionmentioning
confidence: 99%
“…Primary anterior pituitary cells internalize antibodies to the luminal domains of PAM, suggesting post-exocytotic retrieval and the possibility of functional recycling to secretory granules (26,28). In the present study, we used biotinylation to specifically label and follow the fate of the subpopulation of PAM that traverses the plasma membrane.…”
Section: Discussionmentioning
confidence: 99%